Confucianism norms in the establishment of the miniskirt policy in South Korea in 1973 - Maharani, Saskia Dwi Putri; Rostineu, Rostineu (Universitas Pendidikan Indonesia (UPI), 2022)
After the Korean War ended in 1953, Western culture rooted in the United States dominated South Korean society. This study analyses the influence of Confucianism norms on the miniskirt policy in South Korea in 1973. The Miniskirt policy is one of the policies contained in the Minor Offences Act or Gyeongbeomjoecheobeolbeop which was passed in 1973. In this law, one of the violations is overexposure, which refers to women wearing miniskirts. At that time, the police usually carried a ruler on patrol and often stopped women who wore skirts to measure the length. If the skirt worn has a hemline of 17 cm above the knee, the woman will be penalized. This policy was made because the view of the miniskirt does not fit the norms and traditions of the Korean women clothing, which creates controversy. Therefore, the research question in this study is how Confucianism norms justify the miniskirt policy for Korean women. This study uses a descriptive analysis method with the help of literature study. This study aims to explain Confucianism norms as the influence of the establishment of the South Korean miniskirt policy in 1973. The results show that the establishment of the miniskirt policy in 1973 was triggered by Confucianism norms, especially dress etiquette for Korean women which were regulated by Confucian officials. This norm was re-emphasized during the Park Chung-hee era through this policy, where Confucianism was a value that was applied to his government to strengthen the identity of the Korean nation.